2010
DOI: 10.1146/annurev-ecolsys-102209-144712
|View full text |Cite
|
Sign up to set email alerts
|

Putting Eggs in One Basket: Ecological and Evolutionary Hypotheses for Variation in Oviposition-Site Choice

Abstract: Oviposition-site choice is a major maternal effect by which females can affect the survival and phenotype of their offspring. Across oviparous species, the ultimate reasons for females' selection of oviposition sites often differ. We present six hypotheses that have been used to explain nonrandom oviposition-site choice in insects, fish, amphibians, reptiles, and birds: (a) maximizing embryo survival, (b) maximizing maternal survival, (c) modifying offspring phenotype, (d) proximity to suitable habitat for off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
292
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(299 citation statements)
references
References 119 publications
1
292
3
3
Order By: Relevance
“…These apparent preferences may be linked to familiarity of rearing environment that can alter subsequent behaviour in fishes 36,37 . However, they could alternatively be an innate behaviour linked to requirements for optimal habitat, and specifically the requirements for self-protection, egg laying and brood care 38 . Small females may be unable to defend shelter on rock habitat because of competition from large growing females, but they may be favoured on shell habitat as they can escape predators and lay eggs deep enough in shells to avoid the numerous egg predators, including freshwater crabs 26 .…”
Section: Discussionmentioning
confidence: 99%
“…These apparent preferences may be linked to familiarity of rearing environment that can alter subsequent behaviour in fishes 36,37 . However, they could alternatively be an innate behaviour linked to requirements for optimal habitat, and specifically the requirements for self-protection, egg laying and brood care 38 . Small females may be unable to defend shelter on rock habitat because of competition from large growing females, but they may be favoured on shell habitat as they can escape predators and lay eggs deep enough in shells to avoid the numerous egg predators, including freshwater crabs 26 .…”
Section: Discussionmentioning
confidence: 99%
“…By selecting suitable thermal microenvironments, free-living individuals can maintain stable body temperatures near their physiological optimum during activity (Avery 1982;Huey 1982;Angilletta et al 2002;Christian et al 2006). In contrast, the egg-bound embryos of oviparous species (most reptiles) were long assumed to be at the mercy of the nest environment (e.g., Shine et al 1997;Ackerman and Lott 2004;Refsnider and Janzen 2010). Recent work, however, has demonstrated that the embryos of many amniotes-including species of turtle, crocodile, snake, and bird-adjust their positions within the egg in response to thermal gradients, actively moving toward or away from external heat sources (Du et al 2011;Zhao et al 2013;Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Spawning in more protected sites may compose a strategy to decrease predation vulnerability of the couple and their offspring, since predation seems an aspect of major importance for oviposition-site choice in many anurans (Magnusson & Hero, 1991;Refsnider & Janzen, 2010). Therefore, predation may be minimized by access to suitable habitats, which provide resources and conditions for which several males may compete during reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…other anurans, snakes, birds and mammals) (Kluge, 1981;Magnusson & Hero, 1991;Martins et al, 1993). Proximity with reproduction period and sequential filling of suitable habitats may also force some satellite males to build their nests in suboptimal habitats subjected to high levels of predation and drying of water inside nest (Martins & Haddad, 1988;Martins, 1993a;Refsnider & Janzen, 2010). Under such conditions, male reproductive success should decrease owing to lower chances of female oviposition in an unprotected nest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation